The Severity of Primary Dysmenorrhea Pain among Middle Adolescent Students Enrolled at SMA Negeri 5 Surakarta. - Aina Alifyana Devi; Niken Bayu Argahen; Rufidah Maulina; Nurul Jannatul Wahidah; Rizka Ayu Setyani; Fika Lilik Indrawati; Grhasta Dian Perestroika (Universitas Nahdlatul Ulama Surabaya, 2023)
Dysmenorrhea refers to the experience of pain resulting from uterine cramps during menstruation. Typically, this pain arises at the start of the menstrual cycle and persists for several hours or even days until reaching its highest intensity. The prevalence of dysmenorrhea is highest among individuals aged 15 to 25, during their late teenage years and early adulthood. The objective of this study is to present an overview of the level of menstrual pain (dysmenorrhea) among mid-adolescent students attending SMA Negeri 5 Surakarta. The study encompasses all female students at SMA Negeri 5 Surakarta, and a sample of 139 individuals was randomly selected for participation. The mean score was used for data analysis in this research, employing the NRS (Numeric Rating Scale) questionnaire as the research instrument. The results of this study demonstrate an average pain level of 4.89 among female students at SMA Negeri 5 Surakarta, with an average age of menarche at 12 years, an average menstruation duration of 6 days, and an average menstrual cycle of 28 days.